Performance Evaluation of a Custom PID-Based Flight Controller Board for Quadcopter Stabilization - Ahmad Riyad Firdaus; Daipansyah Arya Saputra; Ezha Tri Saputra; Hendawan Soebhakti; Ryan Satria Wijaya (Politeknik Negeri Batam, 2026)
This paper presents the design, implementation, and evaluation of a custom standalone flight controller board for quadcopter stabilization using a cascaded Proportional–Integral–Derivative (PID) control architecture. The hardware integrates an STM32F405 microcontroller, a BMI270 inertial measurement unit (IMU), and a BMP280 barometric sensor to support attitude and altitude control. Experimental evaluations included IMU accuracy testing, rig-based attitude stabilization, and real-flight trials. The IMU achieved average angular errors of ±0,24° (roll), ±0,74° (pitch), and ±0,41° (yaw), indicating reliable orientation measurement. Step-response analysis showed stable transient behavior, with overshoot values of 9,375% for roll, 25% for pitch, and 1,58% for yaw. Static attitude tests yielded mean absolute errors of 0,171° (pitch) and 0,380° (roll). Flight tests confirmed stable attitude and altitude maintenance under real operating conditions. These results demonstrate that the proposed flight controller provides reliable and scalable performance for quadcopter research and development applications.